Unemployment Benefits and Optimal Non-Linear Income Taxation - Per Engström (Uppsala University, Department of Economics, 2003)
This paper explores the rationale for unemployment benefits as a complement to optimal non-linear income taxation. High-skilled workers and low-skilled workers face different exogenous risks of being unemployed. As long as the low-skilled workers face a higher unemployment risk, we find that there is a case for over-insuring the low-skilled, hence the unemployment benefits of the low-skilled should be higher than the pure insurance purpose would prescribe. This effect is likely to prevail in a model with a more realistic treatment of the labor market.
urn:nbn:se:uu:diva-4455
Keywords: H21; J22; J41; J64; 330; Optimal non-linear income taxation; unemployment benefits; Arbeitslosenversicherung; Einkommensteuer; Optimale Besteuerung; Theorie